Murder on the Orient Express - Matthew Ingleby (Opticon1826, 2011)
The late Frank Kermode defined ‘the classic’ as the endlessly re-readable text. Classics energise the critical sphere afresh in each generation by proving themselves open to novel adaptations whilst escaping the confines of any particular interpretation. The plot-driven detective genre, which all too often fakes novelty by rearranging the Cluedo pieces, places an overt structural emphasis on interpretive closure. Threatening to reduce reading to riddle-solving, detective literature would thus appear to be the very antithesis of Kermode’s classically good read.